Ikhlas dalam Hadis Nabi: Rekonstruksi Nilai Spiritual melalui Analisis Tematik Riwayat Ṣaḥĭḥ - Muhamad, Muhamad Nur Insanudin; Rosyadi, Salim (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2025)
Sincerity is the key to every job, whether it is physical or spiritual. This is in accordance with the hadith of the Prophet Muhammad SAW in the narration of Bukhari number 1. In this hadith it is explained that every job depends on its intention, if in his heart it is intended sincerely solely because of Allah and His Messenger then it will be recorded as a good deed by Allah SWT. This study uses a qualitative method based on library research, books, journals and books from sources that are clearly related to the theme of Ikhlas. This study is based on a collection of hadiths of the Prophet Muhammad SAW. This study aims to find out what hadiths discuss sincerity, types of sincerity and how urgent ikhlās is in everyday life. Then, the insincerity that occurs in society is largely influenced by the bad habit of showing off all actions in public (riyā'), the lack of public awareness of the importance of being sincere in everyday life. Finally, preventive efforts that can be done include optimizing community education regarding awareness of being sincere and also instilling knowledge about sincerity in early childhood in the community. The author still realizes that in this study there are still many shortcomings both in the writing and understanding of the author in writing this study. This study is expected to be a motivation for the next generation to develop better in conducting research related to problems that occur in the midst of Islamic society. Keywords: Hadith Perspective, Sincere, Thematic Hadith.